2003
DOI: 10.1152/ajplung.00134.2002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TNF-α gene expression and bioactivity by site-specific transcription factor-binding oligonucleotides

Abstract: The present study investigated transcriptional inactivation of TNF-α gene by nuclear factor-binding oligonucleotides (ON) and their effects on pulmonary inflammatory responses in mice. PCR-based gene mutation and gel shift assays were used to identify specific cis-acting elements necessary for nuclear factor binding and transactivation of TNF-α gene by lipopolysaccharide (LPS). LPS inducibility of TNF-α was shown to require transcriptional activation by NF-κB at multiple binding sites, including the −850 (κ1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…MEFs were stably transfected with the TNF-␣-luciferase reporter plasmid, in which the transcription of the luciferase reporter gene was driven by the mouse TNF-␣ promoter (nucleotides Ϫ1260 to ϩ60) (56,59). We found that the TNF-␣ promoter-driven luciferase activities were significantly induced in wild-type MEFs in a dose-dependent manner but that such induction was dramatically suppressed in p85␣ Ϫ/Ϫ transfectants under the same experimental conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MEFs were stably transfected with the TNF-␣-luciferase reporter plasmid, in which the transcription of the luciferase reporter gene was driven by the mouse TNF-␣ promoter (nucleotides Ϫ1260 to ϩ60) (56,59). We found that the TNF-␣ promoter-driven luciferase activities were significantly induced in wild-type MEFs in a dose-dependent manner but that such induction was dramatically suppressed in p85␣ Ϫ/Ϫ transfectants under the same experimental conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The TNF-␣-luciferase reporter plasmid, in which the transcription of the luciferase reporter gene is driven by the upstream 5Ј-flanking region of the TNF-␣ gene promoter (nucleotides Ϫ1260 to ϩ60), has been described previously (56,59). The NF-B-, AP-1-, and NFATluciferase reporter plasmids were also described previously (23,55).…”
Section: Methodsmentioning
confidence: 99%
“…The production of ROS can stimulate a cytokine cascade through NF-κB-induced transcriptional events, which then induce the expression of TNF-α [31,32]. TNF-α stimulates O 2 •− production in neutrophils and ECs, reportedly via CAPK (ceramide-activated protein kinase), NADPH oxidase [33], XO [34], NOS [35,36] etc.…”
Section: Effect Of Tnf-α On Ros Productionmentioning
confidence: 99%
“…Although mutations in these low-affinity NF-κB sites were reported to reduce LPS inducibility of the human TNF gene by 40–50% in reporter assays [29, 87], these reports were hard to reconcile with studies showing that mutation of κ1 [37] and even deletion of the entire distal promoter [22, 3739, 41] did not impact LPS induction of a human TNF reporter gene. Similarly, in gene reporter assays with the murine TNF promoter, deletion of the distal promoter region [42] and mutation of κB1 (and in some cases, κB3, κB2, and κB2a) had little to no effect on LPS-induced TNF transcription [29, 99]. Thus, there has been no clear functional role demonstrated for these NF-κB motifs in the activation of murine or human TNF gene transcription.…”
Section: Nuclear Factor-κb-independent Tnf Gene Transcriptionmentioning
confidence: 99%